Quality of life and symptom assessment in paraesophageal hernias: a systematic literature review of reporting standards. Issue 7 (13th January 2021) - Patel, Nikhil M; Puri, Aiysha; Sounderajah, Viknesh; Ferri, Lorenzo; Griffiths, Ewen; Low, Donald; Maynard, Nick; Mueller, Carmen; Pera, Manuel; van Berge Henegouwen, Mark I; Watson, David I; Zaninotto, Giovanni; et al.
Summary: Background: Paraesophageal hernias (PEH) present with a range of symptoms affecting physical and mental health. This systematic review aims to assess the quality of reporting standards for patients with PEH, identify the most frequently used quality of life (QOL) and symptom severity assessment tools in PEH and to ascertain additional symptoms reported by these patients not captured by these tools. Methods: A systematic literature review according to PRISMA protocols was carried out following a literature search of MEDLINE, Embase and Cochrane databases for studies published between January 1960 and May 2020. Published abstracts from conference proceedings were included. Data on QOL tools used and reported symptoms were extracted. Results: This review included 220 studies reporting on 28 353 patients. A total of 46 different QOL and symptom severity tools were used across all studies, and 89 different symptoms were reported. The most frequently utilized QOL tool was the Gastro-Esophageal Reflux Disease-Health related quality of life questionnaire symptom severity instrument (47.7%), 57.2% of studies utilized more than 2 QOL tools and 'dysphagia' was the most frequently reported symptom, in 55.0% of studies. Notably, respiratory and cardiovascular symptoms, although less common than GI symptoms, were reported and included 'dyspnea' reported in 35 studies (15.9%). Conclusions: There lacks a QOL assessment tool that captures the range of symptoms associated with PEH. Reporting standards for this cohort must be improved to compare patient outcomes before and after surgery. Further investigations must seek to develop a PEH specific tool, that encompasses the relative importance of symptoms when considering surgical intervention and assessing symptomatic improvement following surgery.